Creative economy education at INSTIKI with business model canvas approach - I Dewa Ayu Agung Tantri Pramawati; I Putu Arya Mulyawan; Kompiang Martina Dinata Putri; Ni Putu Ayu Siska Wulantari (Sean Institute, 2024)
The creative economy relies on invention and creativity, which this research taught pupils. Campuses must foster students' creativity and innovation so they can generate new ideas and solutions. Understanding the creative economy helps students adapt to the changing workplace. Students should understand more about the creative economy ecosystem to engage in learning. Students gain practical experience through Business Model Canvas (BMC) collaborative projects at universities. Data is collected through observation, interviews, and literacy studies in this descriptive qualitative study.INSTIKI creative entrepreneurship students are the focus of research. This research seeks to maximize local cultural capital, traditions, and natural resources for creative products and services. As they learn more about the creative economy, students are expected to sell local products, consider environmental implications, implement environmentally responsible business practices, and enhance their living conditions. Education introduces students to the creative economic ecosystem, which can boost their engagement in learning, according to this study. Students' creative ideas will be designed and developed into collaborative initiatives using the Business Model Canvas (BMC) approach at universities to give them real experience.